Coaches` and players` perceptions of training dose: not a perfect match - Brink, M. S.; Frencken, W. G. P.; Jordet, G.; Lemmink, K. A. P. M. (International Journal of Sports Physiology and Performance, 2014)
Purpose: The aim of the current study was to investigate and compare coaches` and players` perceptions of training dose for a full competitive season. Methods: Session rating of perceived exertion (RPE), duration, and training load (session RPE × duration) of 33 professional soccer players (height 178.2 ± 6.6 cm, weight 70.5 ± 6.4 kg, percentage body fat 12.2 ± 1.6) from an under-19 and under-17 (U17) squad were compared with the planned periodization of their professional coaches. Before training, coaches filled in the session rating of intended exertion (RIE) and duration (min) for each player. Players rated session RPE and training duration after each training session. Results: Players perceived their intensity and training load (2446 sessions in total) as significantly harder than what was intended by their coaches (P < .0001). The correlations between coaches` and players` intensity (r = .24), duration (r = .49), and load (r = .41) were weak (P < .0001). Furthermore, for coach-intended easy and intermediate training days, players reported higher intensity and training load (P < .0001). For hard days as intended by the coach, players reported lower intensity, duration, and training load (P < .0001). Finally, first-year players from the U17 squad perceived training sessions as harder than second-year players (P < .0001). Conclusion: The results indicate that young elite soccer players perceive training as harder than what was intended by the coach. These differences could lead to maladaptation to training. Monitoring of the planned and perceived training load of coaches and players may optimize performance and prevent players from overtraining.